Policies and Responsibilities of Government Officials during the Covid-19: The Problem of Interpreting the Phrase of Good Faith in Law Number 2 of 2020 - Darsinah, Darsinah; Hasyim, Achmad Dardiri; Mulyo, Mufrod Teguh (UIN Sunan Kalijaga, 2022)
Abstract: Article 27 Paragraph (2) Law Number 2 of 2020 introduces the term